Instrumented activity and semiotic mediation: two frames to describe the conjecture construction process as curricular organizer (2013)
We document part of the process through which conjectures produced by students, with the aid of the dynamic geometry software Cabri, when they solve proposed geometric problems, become a curriculum organizer in the classroom. We first focus on characterizing students¿ instrumented activity recurring to utilization schema (Rabardel, 1995, in Bartolini Bussi and Mariotti, 2008), and then describe the teacher¿s content management through which the ideas produced by the students become key elements of knowledge construction.